Stochastic fluid dynamics simulations of the velocity distribution in protoplasmic streaming - Egorov, Vladislav; Maksimova, Olga; Andreeva-Sussin, Irina; Koibuchi, Hiroshi; Hongo, Satoshi; Nagahiro, Shinichiro; Ikai, Toshiyuki; Nakayama, Madoka; Noro, Shuta; Uchimoto, Tetsuya; Rieu, Jean-Paul (Physics of Fluids, 2020)
International audience Protoplasmic streaming in plant cells is directly visible in the cases of Chara corallina and Nitella flexilis , and this streaming is understood to play a role in the transport of biological materials. For this reason, related studies have focused on molecular transportation from a fluid mechanics viewpoint. However, the experimentally observed distribution of the velocity along the flow direction x, which exhibits two peaks at V x = 0 and at a finite V x (≠0), remains to be studied. In this paper, we numerically study whether this behavior of the flow field can be simulated by a 2D stochastic Navier–Stokes (NS) equation for Couette flow in which a random Brownian force is assumed. We present the first numerical evidence that these peaks are reproduced by the stochastic NS equation, which implies that the Brownian motion of the fluid particles plays an essential role in the emergence of these peaks in the velocity distribution. We also find that the position of the peak at V x (≠0) moves with the variation in the strength D of the random Brownian force, which also changes depending on physical parameters such as the kinematic viscosity, boundary velocity, and diameter of the plant cells.I. INTROD